2016
DOI: 10.1080/13691058.2015.1133846
|View full text |Cite
|
Sign up to set email alerts
|

Being a gay man in Turkey: internalised sexual prejudice as a function of prevalent hegemonic masculinity perceptions

Abstract: This paper examines expressions and experiences of internalised sexual stigma with respect to definitions of masculinity and identity conflicts through a thematic analysis of life-history narratives of 14 self-identified gay men living in Turkey. The analysis reveals that internalised sexual prejudice emerges when widely accepted hegemonic masculinity ideology is 'violated' by being gay. Participants' narratives indicate that their construction of masculinity is a vigorous process established via encounters wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 38 publications
1
21
0
1
Order By: Relevance
“…Typically, Grindr is used by MSM to find partners for dating, friendship, or sex, although its reputation is for the latter (i.e., as a hook-up application; Gudelunas, 2012). The few studies that have used Grindr have reported that the application provides easy access to willing and hard-to-reach research samples (Burrell et al, 2012;Eslen-Ziya & Koc, 2016;Koc, 2016).…”
Section: Grindr: a Location-based Application Designed For Men Who Hamentioning
confidence: 99%
“…Typically, Grindr is used by MSM to find partners for dating, friendship, or sex, although its reputation is for the latter (i.e., as a hook-up application; Gudelunas, 2012). The few studies that have used Grindr have reported that the application provides easy access to willing and hard-to-reach research samples (Burrell et al, 2012;Eslen-Ziya & Koc, 2016;Koc, 2016).…”
Section: Grindr: a Location-based Application Designed For Men Who Hamentioning
confidence: 99%
“…Although this is changing in some parts of the world, and being a male in Turkey still requires one to be heterosexual and to endorse the features of hegemonic masculinity, according to the perspectives of heterosexual men (Boratav, Fişek, & Ziya, ; Sancar, ), and gay men (Koc & Eslen‐Ziya, ). Gay identity, on the other hand, is a threat to one's male identity, as it is perceived to violate the requirements of hegemonic masculinity even for gay men themselves (Eslen‐Ziya & Koc, ). Hence, it is possible to say that gay and male identities are incompatible in Turkey, and that Turkish gay men are likely to experience conflict between their sexual and gender identities, as discussed by Franklin () and Herek ().…”
Section: Introductionmentioning
confidence: 99%
“…Jaspal and Cinnirella () suggested that gay‐affirmative social contexts provide feelings of belonging and increased well‐being for those who have potentially incompatible identities (i.e., British Muslim gay men), and we suggest that global identification might function to create a gay‐affirmative social context for gay–male Turkish individuals. People who identify with globalized Western culture might gain access to positive aspects of gay identity, that are otherwise unavailable in a culture where negative antigay attitudes are prevalent (Anderson & Koc, ) and gay men report experiencing internalized sexual prejudice as a function of violating male gender roles (Eslen‐Ziya & Koc, ). Accordingly, we expect that the more strongly Turkish gay men identify as ‘global citizens’, the more they should experience their gay and male identities as compatible, with corresponding benefits for their psychological well‐being.…”
Section: Introductionmentioning
confidence: 99%
“…Dominant cultural conceptions of manhood in Turkey, also echoed by gay men themselves, maintained the importance of masculinity and the rejection of femininity (Bolak-Boratav, Fisek, & Ziya, 2014;Erol & Ozbay, 2013). Accordingly, gay men expressed internalised sexual prejudice towards other gay men (Eslen-Ziya & Koc, 2016). Since the ideal way of being a 'real man' requires them to be heterosexual and rejects both femininity and homosexuality, Turkish gay men continue to feel a conflict between their gay and male identities (Erol & Ozbay, 2013;Eslen-Ziya & Koc, 2016).…”
mentioning
confidence: 99%
“…For example, in a society where traditional gender roles are valued, it could be easier to integrate sexual and gender identities if one is heterosexual and male; in contrast, it could be difficult to accept and express a gay-male identity, because traditional masculine norms prescribe heterosexuality and rejection of homosexuality in most countries (Connell, 2005;Eslen-Ziya & Koc, 2016;Herek, 1986). Most men try to live up to these masculine ideals and negotiate their own masculinity with the prescribed norms (Pleck, 1995;Wilson et al, 2010); yet, the identities of gay men may be inherently threatened because their sexual identity entails homosexuality whereas a masculine gender identity prescribes rejection of homosexuality in many cultural contexts (Boratav, Fisek, & Eslen-Ziya, 2014;Wilson et al, 2010).…”
mentioning
confidence: 99%